2018
DOI: 10.3389/fphar.2018.00068
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Activates AMPK to Inhibit Metastasis of Colorectal Cancer

Abstract: Rosmarinic acid (RA) has been used as an anti-inflammatory, anti-diabetic, and anti-cancer agent. Although RA has also been shown to exert an anti-metastatic effect, the mechanism of this effect has not been reported to be associated with AMP-activated protein kinase (AMPK). The aim of this study was to elucidate whether RA could inhibit the metastatic properties of colorectal cancer (CRC) cells via the phosphorylation of AMPK. RA inhibited the proliferation of CRC cells through the induction of cell cycle arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 64 publications
6
67
3
Order By: Relevance
“…Besides PPARγ, AMPK is also known to regulate lipolytic enzymes in adipose tissue (Kim et al., ). Even though the effect of PE on AMPK was not evaluated in our study, previous reports have suggested that rosmarinic acid activates AMPK pathway in different tissues to exert it beneficial effects (Abe, Saito, & Nogata, ; Han, Kee, & Hong, ; Jayanthy, Roshana Devi, Ilango, & Subramanian, ; Vlavcheski, Naimi, Murphy, Hudlicky, & Tsiani, ). Therefore, we presume that the increased mRNA expression of ATGL and HSL, despite of the reduced PPARγ expression will be due to the activation of AMPK pathway.…”
Section: Resultsmentioning
confidence: 90%
“…Besides PPARγ, AMPK is also known to regulate lipolytic enzymes in adipose tissue (Kim et al., ). Even though the effect of PE on AMPK was not evaluated in our study, previous reports have suggested that rosmarinic acid activates AMPK pathway in different tissues to exert it beneficial effects (Abe, Saito, & Nogata, ; Han, Kee, & Hong, ; Jayanthy, Roshana Devi, Ilango, & Subramanian, ; Vlavcheski, Naimi, Murphy, Hudlicky, & Tsiani, ). Therefore, we presume that the increased mRNA expression of ATGL and HSL, despite of the reduced PPARγ expression will be due to the activation of AMPK pathway.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, rosmarinic acid was the major phenolic component in our EEOS. Rosmarinic acid inhibited colon cancer invasion (Xu et al, 2010) and colorectal cancer metastasis (Han et al, 2018) by inhibiting MMP-2 and MMP-9 activity. These findings imply that the rosmarinic acid in EEOS may be a key factor in suppressing HNSCC cell invasion and MMP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rosmarinic acid was the major phenolic component in our EEOS. Rosmarinic acid inhibited colon cancer invasion [30] colorectal cancer metastasis [31] by inhibiting MMP-2 and MMP-9 activity. These findings imply that the rosmarinic acid in EEOS may be a key factor in suppressing HNSCC cell invasion and MMP activity.…”
Section: Discussionmentioning
confidence: 99%